Investigation on Co–Modified NixMgyO solid solutions for hydrogen production from steam reforming of acetic acid and a model blend - Luo, Xiang; Hong, Yu; Shi, Kaiqi; Yang, Gang; Pang, Chengheng; Lester, Edward; Jiang, Lei; Wu, Tao (Wiley-Blackwell, 2019)
This paper is focused on the Co-modified NixMgyO solid solutions (10wt% Ni, 2-6wt% Co) for the steam reforming of acetic acid and a model blend. The pristine rocksalt structured NixMgyO solid solution and the modified NixMgyO-Co catalysts were synthesized via hydrothermal method and co-impregnation. The activity of the catalysts was evaluated in the temperature range of 500-800 °C with a steam/carbon molar ratio of 3 and a gas hourly space velocity (GHSV) of 57,000 h-1. Low cobalt content (Co loading = 2wt%) catalysts exhibited significant promotion of H2 yield via enhancement of both water-gas shift (WGS) reaction and methane decomposition. A 30-hour test at 700 °C achieved excellent acetic acid conversion rate and H2 yield of 99.1% and 86.9%, respectively. However, the catalysts with higher cobalt loading (Co loading ≥ 4wt%) suffered a much quicker deactivation mainly due to carbon deposition. In addition, the catalysts were also tested on a model blend combined acids, alcohols and aromatic species and exhibited outstanding performance with carbon conversion above 90% and H2 yield above 70% for 100 h.